THE DISTRIBUTION OF BATS OF GENUS LASIURUS (VESPERTILIONIDAE) IN COLOMBIA, WITH NOTES ON TAXONOMY, MORPHOLOGY AND ECOLOGY (2015)
In order to clarify the distribution of bats of the genus Lasiurus in Colombia, we performed a morphological study of 49 specimens from four Colombian collections. Our review confirms the presence of three species in Colombia (L. blossevillii, L. cinereus, and L. ega) with distribution in all natural regions that include six of the nine biogeographic provinces. These species can be easily differentiated based on external and cranial characters. Lasiurus cinereus is the largest species (forearm length 52 mm) and L. blossevillii is the smallest (forearm 42 mm); L. ega has a distinctive skull shape with a developed sagittal crest. While previous literature make claims that L. egregius and L. castaneus occur in Colombia, our analysis found no support for this and even contradicts the evidence cited for their presence in the country. We demonstrate that one specimen attributed to L. egregius in literature corresponds to a misidentified L. blossevillii. Furthermore, we found that there are not any specimens of L. castaneus from the Department of Cundinamarca despite several reports in the literature. The status of subspecies in Colombia remains controversial and more specimens are needed to determine whether there are clear distinctions between forms in any geographical region. Most of the specimens examined were males and in some cases, were collected opportunistically from dead individuals found in cities in the Andean region.